Regional expression of Pax7 in the brain of Xenopus laevis during embryonic and larval development - Sandra eBandín; Ruth eMorona; Nerea eMoreno; Agustín eGonzález (Frontiers Media S.A., 2013)
Pax7 is a member of the highly conserved Pax gene family that is expressed in restricted zones of the central nervous system during development, being involved in early brain regionalization and the maintenance of the regional identity. Using sensitive immunohistochemical techniques we have analyzed the spatiotemporal pattern of Pax7 expression in the brain of the anuran amphibian Xenopus laevis, during development. Pax7 expression was first detected in early embryos in the basal plate of prosomere 3, roof and alar plates of prosomere 1 and mesencephalon, and the alar plate of rhombomere 1. As development proceeded, Pax7 cells were observed in the hypothalamus close to the catecholaminergic population of the mammillary region. In the diencephalon, Pax7 was intensely expressed in a portion of the basal plate of prosomere 3, in the roof plate and in scattered cells of the thalamus in prosomere 2, throughout the roof of prosomere 1, and in the commissural and juxtacommissural domains of the pretectum. In the mesencephalon, Pax7 cells were localized in the optic tectum and, to a lesser extent, in the torus semicircularis. The rostral portion of the alar part of rhombomere 1, including the ventricular layer of the cerebellum, expressed Pax7 and, gradually, some of these dorsal cells were observed to populate ventrally the interpeduncular nucleus and the isthmus (rhombomere 0). Additionally, Pax7 positive cells were found in the ventricular zone of the ventral part of the alar plate along the rhombencephalon and the spinal cord. The findings show that the strongly conserved features of Pax7 expression through development shared by amniote vertebrates are also present in the anamniote amphibians as a common characteristic of the brain organization of tetrapods.